Eclectisch en toch nieuw. De uitvinding van het Belgisch parlement in 1830-1831 - Smaele, H. De (BMGN - Low Countries Historical Review, 2005)
Eclectic yet still new. The creation of the Belgian parliament in 1830-1831The Belgian Constitution of 1831 consisted mainly of clauses borrowed from older constitutions. Besides, most members of the Constituent Assembly were guided by the British parliamentary model, which was also promoted by French liberal authors as a welcome alternative to republicanism. Nevertheless, it departed from the British liberal model on some crucial issues and reverted to the French republican model once again. In this sense, the Belgian Constitution was indeed eclectic. Nevertheless, the combination was both refreshingly innovative and explicit in that it excluded the holistic concepts of ‘nation’ that were present in both the British and the French models. This article is part of the special issue 'Parlementen in de Nederlanden'.